Philanthropic Support of Historically Black Colleges and Universities in the 21st Century - Marybeth Gasman; Andrés Castro Samayoa; Kem Benyehudah; Anthony Fowlkes (Ali Khorsandi Taskoh, 2022)
This paper focuses on philanthropic donations to Historically Black Colleges and Universities (HBCUs) during the first two decades of the twenty-first century, from 2003 to 2021. We examine these years to capitalize on the census of available years in our data source and to also examine the shifts in foundation giving over time. We offer a descriptive overview detailing which philanthropic organizations have provided the largest share of support, the HBCUs receiving these gifts, and the areas for support targeted through these donations. In doing so, our manuscript offers a novel contribution to scholarship on philanthropic giving to HBCUs using an original database of major U.S. philanthropies' annual reports joined with secondary data from the Integrated Postsecondary Education Data System (IPEDS) maintained by the National Center for Education Statistics.